ADHD and academic performance: a description of current knowledge - Juliana Campos Schmitt; Eunice Maria Godinho Morando (INFAD, 2017)
The aim of this review of the literature was to identify and analyze the Brazilian studies in the last 10 years on the relationship between Attention Deficit Hyperactivity Disorder (ADHD) and the academic achievement of children, adolescents, and adults. Method: A search of the scientific literature was conducted in the databases: Pepsic, Redalyc, and Scielo using the descriptors: “ADHD and school achievement”; “ADHD and academic achievement”;”ADHD and school performance”;”ADHD and academic performance”. It was considered publications from January 1, 2006, through December 31, 2016. Results: The studies demonstrated that there has been very little research in the area, it has been found 217 studies and only 9 studies analyzed after the application the exclusion criteria. Conclusion: It is believed that the ADHD has a negative influence on the academic achievement, it has been found only 3 studies that evaluated the academic achievement directly, the others studies evaluated variables that possibly influence the academic achievement.